German emigre economists and the internationalisation of economics - Tribe, Keith (2001)
Comenta el libro editado por Harald Hagemann y Claus-Dieter Krohn, "Biographical guide to the emigration of german-speaking economists after 1933", K.G. Sauer, Munich 1999, 2 vols.
Keywords: Economista; Emigración; Alemania; Austria